SMART ABDOMEN MODEL AS CLINICAL LEARNING MEDIA IN IMPROVING MIDWIFERY STUDENT COMPETENCE IN POSTPARTUM CARE - Herlyssa; Elly Dwi Wahyuni; Jujun Dwi Astuti; Sri Rahayu (SEAJOM: The Southeast Asia Journal of Midwifery, 2022)
This study aims to determine the effectiveness of the "SMART" abdominal model as a clinical learning media in increasing student competence for assessing uterine fundal height in postpartum mothers. This research is a quasi-experimental research with The Posttest-only Control Group Design. The study was conducted in two groups, namely the treatment group and the control group. The population of this study was all students of the third semester of midwifery D III study program in two health polytechnic in Indonesia. The intervention group consisted of some students who were given assistance in using the "SMART" abdominal model to assess the height of the uterine fundus in postpartum mothers in simulated patients, while the control group consisted of some students without assistance in using the "SMART" abdominal model to assess height uterine fundus in postpartum women on a conventional abdominal model (Zoe's abdominal model). The total sample was 120 people, which were divided into 60 people from one Poltekkes as the control group and 60 people from another Poltekkes as the intervention group. The sampling technique was purposive sampling. Data was collected through questionnaires, and observation. The type of data in this study is primary data. Data analysis uses Kai Square. The SMART abdominal model supports the achievement of learning competencies by 81.4%. There was no significant difference in competence when students used the SMART abdominal model on simulated patients or paired them with Zoe's abdominal model. For this reason, innovation and creativity of lecturers are needed in supporting the achievement of subject learning through the development of learning models and technology. In supporting the wider use of the model as a form of downstreaming research products that are integrated into the dharma of education, it is necessary to socialize and disseminate the SMART abdominal model and promote efforts through collaboration with industry and MSMEs.